Enhanced CDM model accounting of stress triaxiality and Lode angle for ductile damage prediction in metal forming. (February 2021) - Zhang, Kai; Badreddine, Houssem; Hfaiedh, Naila; Saanouni, Khemais; Liu, Jianlin
This paper deals with the prediction of ductile damage based on CDM approach fully coupled with advanced elastoplastic constitutive equations. This fully coupled damage model is developed based on the total energy equivalence assumption under the thermodynamics of irreversible processes framework with state variables. In this model, the damage evolution is enhanced by accounting for both stress triaxiality and Lode angle. The proposed constitutive equations are implemented into Finite Element (FE) code ABAQUS/Explicit through a user material subroutine (VUMAT). The material parameters are determined by the hybrid experimental-numerical method using various tensile and shear tests. Validation of the proposed model has been done using different tests of two aluminum alloys (Al6061-T6 and Al6014-T4). Through comparisons of numerical simulations with experimental results for different loading paths, the predictive capabilities of the proposed model have been shown. The model is found to be able to capture the initiation as well as propagation of macro-crack in sheet and bulk metals during their forming processes.